PENDIDIKAN DALAM AL-QURâAN: KAJIAN KONSEP TARBIYAH DALAM MAKNA AL-TANMIYAH PADA Q.S. AL-ISRA: 23-24 - Nurul Wathoni, Lalu Muhammad (Jurnal Pendidikan Guru, 2017)
Personality can be formed through all the experiences and values that are absorbed in thegrowth and development, especially in the first years of age. Therein lies the importancetarbiyyah within the meaning tanmiyah (growth and development). That is a concept ofpersonality formation of children through the cultivation of religious values correspondingguidance of the Koran. So, parents who cultivate the mental physical and mental psychicchild begins, God gives the concept of education is based on the growth process (tanmiyah) inQ.S. al-Isra: 23-24. In this writers research using library research (library research). Theresults of the study concept tarbiyah within the meaning of al-tanmiyah on Q.S. Al-Isra: 23-24indicates that the process of educational development in children is done by plantingkeimanaan values and planting moral values. Planting values of faith including; introduce thename of Allah and His creation, introducing the Prophet and behavior, to teach obedience toAllah and His Messenger. As for planting cultivate moral values in children include; Filial toparents, helping each other, praying in his favor, keeping jani, honest, sincere, kind word,worthy, noble, and gentle to parents and others, Allah forbid servants put out words thatoffend both parents as yell, scold, scold and muddying the feelings of both.